Termotechnical Characteristics Determination of Enclosing Structures for Hydrates Storage - Kutnyi, Bogdan; ., . (International Journal of Engineering and Technology, 2018)
In many countries around the world, gas hydrates use is seen as a promising alternative source of energy. The industrial infrastructure gas hydrates use requires the creation of reliable means for their storage and transportation.In the paper the research installations schemes and the dissociated gas temperature regime hydrate experimental study results are given. The surface and propane hydrate deep layers temperature regime, which decomposes under atmospheric pressure, is analyzed. Convective and radiant heat transfer at the hydrate storage reservoir inner surface is considered and the temperature at the gas hydrates surface is determined. The method for determining the resistance to the tent heat transfer is developed and the dependence for the propane hydrate dissociation intensity is established. The research results can be used to reduce gas losses during gas hydrates storage and transportation under nonequilibrium conditions.Â Â
Keywords: dissociation rate; gas hydrates; hydrate storage; resistance to heat transfer.